ACE2 and RAAS: Therapeutic intervention point for COVID-19 - Dhungel, Kshitiz Upadhyay (Janaki Medical College Journal of Medical Science, 2021)
COVID-19 has caused widespread mortality and morbidity and significant economic disruption. Several potential therapeutic and/ or preventive approaches to address the pandemic are being worked out, a few effective vaccines are under clinical trials and few vaccines has been approved but still the expected result has not been achieved. Some Spiritual Leader claims it to be natural process and can be protected by chant of Mantra 'Pujya Anakarananta Nirakar niranjan shivajyoti mahamanav pita'.Renin-Angiotensin-Aldosterone System (RAAS) is no more a mere research area in cardio-pulmonary and renal physiology alone but has gained focus as an infection and therapeutic point for COVID-19. This article discusses about ACE2 receptor as a centre point of infection of SARS-CoV-2 and also suggests it as the therapeutic intervention point for COVID-19.